META-ANALISIS PENINGKATAN KETERAMPILAN MENULIS DENGAN STRATEGI SUGESTOPEDIA - Megawati Megawati; Didin Widyartono; Dedi Risaldi (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aimed to describe the effect of the suggestopedia strategy on language learning, specifically on literary and non-literary writing skills. This research is a meta-analysis that quantitatively synthesises previous research findings. Data and data sources were obtained from accredited national scientific articles that met the inclusion criteria, namely, those discussing the application of suggestopedia in writing instruction, employing a quantitative approach, and presenting pretest and posttest score data. The data analysis technique employed a comparative method to calculate the percentage increase in learning outcomes, followed by a parametric statistical test, paired sample t-test, to examine the significance of the difference in mean scores before and after the implementation of the suggestopedia strategy. The results show that the implementation of the suggestopedia strategy can improve students' writing skills, with the range of improvement categorised from low to very high. The students' average scores experienced a significant increase after the treatment. The results of the paired sample t-test confirmed a significant difference in writing skills before and after the implementation of the suggestopedia strategy. The implications of this study recommend that Indonesian language teachers integrate the suggestopedia strategy by varying relaxation music and classroom decorations that support a conducive learning atmosphere. Schools also need to support teacher training on the systematic implementation of suggestopedia steps to optimise the improvement of students' writing skills.